2023
DOI: 10.3389/fmicb.2023.1273444
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early colonized gut microbiota on the growth performance of suckling lambs

Hanjie Xiao,
Hui Yan,
Peizhi Tian
et al.

Abstract: The early colonized gut microbiota during the newborn period has been reported to play important roles in the health and immunity of animals; however, whether they can affect the growth performance of suckling lambs is still unclear. In this study, a total of 84 newborn lambs were assigned into LF-1 (top 15%), LF-2 (medium 70%), and LF-3 (bottom 15%) groups according to their average body weight gain at 30 days of age. Fecal samples of lambs (LF) as well as feces (MF), vagina (VAG), colostrum (COL), teat skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Some members of the genus Fusobacterium are capable of fermentative metabolism in anaerobic environments to produce organic acids, which might play a positive role in the metabolism of nutrients in the gut ( Ma et al, 2022 ). When studying the impact of early colonization of the gut microbiota on growth performance, it was found that Fusobacterium could significantly increase the growth performance of lambs ( Xiao et al, 2023 ). An increasing number of studies have shown a close relationship between Fusobacterium and immune regulation, and Fusobacterium intervenes in the occurrence of diseases by regulating the innate immune system ( Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some members of the genus Fusobacterium are capable of fermentative metabolism in anaerobic environments to produce organic acids, which might play a positive role in the metabolism of nutrients in the gut ( Ma et al, 2022 ). When studying the impact of early colonization of the gut microbiota on growth performance, it was found that Fusobacterium could significantly increase the growth performance of lambs ( Xiao et al, 2023 ). An increasing number of studies have shown a close relationship between Fusobacterium and immune regulation, and Fusobacterium intervenes in the occurrence of diseases by regulating the innate immune system ( Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Lysinibacillus was also found in the intestine of various breeds of sheep [74]. MDS analysis was performed to compare the fecal microbiota of the studied sheep with sheep from Hebei Province, China [78]. As shown in Figure S6 (III), there was a distinct clustering of fecal microbial community samples from sheep of the Buryat population and sheep from Hebei Province, China.…”
Section: The Core Fecal Microbiota Of Nomadic Animals (Deer Yaks Shee...mentioning
confidence: 98%